(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to determine the relationship between stress and fatigue with nurses’ work productivity at the XYZ clinic. The method used is quantitative correlational non-experimental. The results showed that 63.3% of nurses experienced moderate stress (mean 32.07), 63.3% moderate fatigue, 36.7% high (mean 100.6), 46.7% low productivity, and 36.7% very low (mean 29.67). Stress was not significantly related to productivity (r = 0.327; p = 0.078), while fatigue had a significant relationship (r = 0.619; p = 0.000). In conclusion, there is no significant relationship between stress and work productivity and an essential relationship between fatigue and nurses’ work productivity at the XYZ clinic. Keywords: Fatigue, Nurses, Work Productivity, Stress